Effective Education Funding Strategies to Increase Student Achievement - Haryaka, Usfandi; Chairiyah, Siti Sri; Khayati, Nur; Hanifah, Evy; Merliana, Merliana (Edumaspul: Jurnal Pendidikan, 2024)
This study examines the allocation and distribution of education funding in Indonesia and evaluates the effectiveness of funded programs in improving student quality and achievement. The data were gathered from official sources and subjected to quantitative and qualitative analysis. The findings indicate that an increase in funding for senior secondary education is associated with an increase in school enrollment and a reduction in dropout rates. The Indonesia Smart Program (PIP) demonstrates that targeted financial assistance can facilitate enhanced academic achievement, particularly among students from disadvantaged backgrounds. However, challenges in program implementation, such as delays in disbursement and complicated administrative processes, reduce its overall effectiveness. The study proposes increasing funding allocation for higher education, strengthening monitoring and evaluation systems, and simplifying administrative processes to ensure that the funds are distributed to the intended recipients. Moreover, the study suggests collaboration with the private sector and non-governmental organizations (NGOs) should be pursued. However, the study's limitations include a lack of longitudinal data and geographical coverage, which may not fully reflect the conditions in Indonesia. Further research is recommended to expand the coverage scope and analyze the long-term impact of education funding programs.